Kompetensi Guru dalam Menghadapi Revolusi Industry 4.0 - Ngafifurrohman (Jurnal Kependidikan, 2023)
Abstract The industrial revolution 4.0 has affected various areas of life. In this era, the physical, digital and biological worlds are merged. Many human workers have been replaced by machines because of the automation of various services and the existence of artificial intelligence. The influence of the industrial revolution 4.0 also has an impact on the world of education, so teachers as professional educators must prepare themselves with various competencies to face this progress. The purpose of this study is to find teacher competence in facing the industrial era 4.0. The method used is literature study. The results of the study show that teacher competencies that must be prepared in facing the industrial revolution 4.0 are: 1) mastering the 4C competencies, namely critical thinking, collaborative, communicative, and creative. 2) educational competence, 3) competence for technological commercialization, 4) competence in globalization, 5) competence in the future, 6) counselor competence Keywords: teacher competency, learning, industrial revolution 4.0 .